The United States Department of Labor a story of workers, unions, and the economy - Terrell, John Upton 1900- (New York Meredith Press, 1968)
Describes the historical background of labor in the United States and the events which led to the acceptance of unions and the creation of a labor department. Also explains the organization and duties of this department and its place in the American economy.
Keywords: United States. -- Dept. of Labor